2020
DOI: 10.2196/19013
|View full text |Cite
|
Sign up to set email alerts
|

Exploring eHealth Literacy and Patient-Reported Experiences With Outpatient Care in the Hungarian General Adult Population: Cross-Sectional Study

Abstract: Background Digital health, which encompasses the use of information and communications technology in support of health, is a key driving force behind the cultural transformation of medicine toward people-centeredness. Thus, eHealth literacy, assisted by innovative digital health solutions, may support better experiences of care. Objective The purpose of this study is to explore the relationship between eHealth literacy and patient-reported experience me… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 63 publications
1
9
0
1
Order By: Relevance
“…Firstly, respondents with secondary and tertiary education were slightly overrepresented. Such differences are commonly observed for online sampling methods, fairly similar results have been published before [12]. Therefore, the effect of the difference in educational level on our results is considered negligible.…”
Section: Plos Onesupporting
confidence: 85%
“…Firstly, respondents with secondary and tertiary education were slightly overrepresented. Such differences are commonly observed for online sampling methods, fairly similar results have been published before [12]. Therefore, the effect of the difference in educational level on our results is considered negligible.…”
Section: Plos Onesupporting
confidence: 85%
“…Studies have shown that individuals with greater levels of e-health literacy are linked to regular online searches for health information [ 45 ], as well as greater frequency of web-based health-seeking actions [ 46 ]. Individuals with better e-health literacy can acquire more accurate health-related information, evaluate the quality of information more properly, have better self-management capacity, connect with healthcare practitioners more effectively, and engage in treatment and nursing decision-making [ 47 , 48 ]. Furthermore, in the case of the COVID-19 pandemic, the higher the level of e-health literacy, the greater the willingness to receive vaccination and the better the compliance with public health guidelines [ 49 ].…”
Section: Analysis Of Research Focus In E-health Literacymentioning
confidence: 99%
“…The online sample of 1000 respondents represented well the Hungarian adult population considering sex, age, type of settlement, and region of residence. A comparison of the distribution of the sample with the Hungarian general population based on the last census in 2011 is available in [ 15 ]. Of the 1000 participants, 695 individuals had an outpatient consultation at a family doctor, public specialist, or private specialist within the 12 months preceding data collection.…”
Section: Resultsmentioning
confidence: 99%
“…This was a cross-sectional descriptive study in Hungary, using data collected in 2019 via a web-based survey ‘Patient experiences in health care.’ The survey had three main modules: ‘eHealth literacy’ [ 15 ], ‘Shared decision-making’ [ 16 ], and ‘Patient-reported experience measures’ [ 17 , 18 ]. From the ‘Patient-reported experience measures’ module, we selected questions on waiting times as the focus, namely, on a set of patient-reported experience measures proposed by the OECD [ 5 ].…”
Section: Methodsmentioning
confidence: 99%